Mother–Infant Interaction During Postpartum Depression: A Metaphor Analysis. Issue 2 (June 2020) - Beck, Cheryl T.
Background: Reported in quantitative studies is the negative impact that postpartum depression can have on mother–infant bonding. Metaphors can enhance mothers' communication with their health-care providers that cannot be captured by medical terminology and provide mothers a different voice to explain their experiences interacting with their infants. Purpose: The aim of the study was to identify the metaphorical expressions used by women to describe their interactions with their infants during postpartum depression. Methods: Secondary qualitative data analysis of three primary qualitative data sets of postpartum depression was conducted. The specific type of secondary qualitative analysis used was cross validation where multiple data sets from different studies are compared to expand the results of each individual study to make a more general claim. Data analysis involved using the Metaphor Identification Procedure. Results: Identified were eight metaphors used by mothers to describe their interactions with their infants during their postpartum depression: a thief, a robot, enveloping fogginess, being at the races, an actor, an erupting volcano, skin crawling, and a wall. Conclusions: Being attentive to metaphors mothers use can provide a unique approach to helping nurses identify vulnerable mother–infant dyads during postpartum depression.